Digitalization, and Digital Transformation in MSMEs in Turkey - Eyup Kahveci (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
By analyzing the secondary data, the adoption and utilization of ICT and Digital Technologies (DT) have emerged as key factors in their competitiveness and performance in Turkey. Here are some key findings: Larger driving enterprises tend to have higher technology adoption rates, and there is increasing awareness among MSMEs about the need for digital transformation. MSMEs in Turkey are becoming more aware of the importance of technology adoption and digital transformation for competitiveness. The COVID-19 pandemic has accelerated digitalization and increased the use of digital platforms, such as e-commerce and digital banking. E-commerce marketplace websites or apps are preferred over enterprises' own websites or applications for e- sales due to convenience, customer reach, and advertising campaigns.